Detection of ethyl glucuronide in blood spotted on different surfaces - Winkler, Michaela; Kaufmann, E.; Thoma, D.; Thierauf, A.; Weinmann, W.; Skopp, Gisela; Alt, A. (Forensic science international, 2011)
This study aims to show that sensitive detection of ethyl glucuronide in dried blood spotted onto various surfaces after a period of 24h is feasible. At present, there is insufficient information how tightly ethyl glucuronide (EtG) binds to various materials and how easily it can be eluted. 4ml aliquots of blood samples obtained from seven volunteers after consumption of alcoholic beverages were applied to six different surfaces. After drying and a 24h-storage at 20±2°C the samples were re-dissolved in water, and EtG was subsequently analyzed by a LC-MS Paul-type ion trap. A comparison was made between dried and corresponding fluid samples. EtG was detectable in all subjects’ samples following consumption of alcohol. EtG was also detectable after a storage time of four weeks at 4°C in whole blood that had been preserved with EDTA. EtG was detectable in all samples dried on different surfaces and its concentration remained relatively constant irrespective of the particular condition of the material. Detection of EtG in blood spots from the scene may indicate recent alcohol consumption in cases where collection of blood remained undone or could not be performed.
Gesehen am 07.11.2022